Magnetic target and magnetic target assembly
A magnetic material target with controlled oxide distribution and size, composed of CO, Pt, Cr, Ru, and Ti, addresses the issue of oxide particle formation during sputter film formation, enhancing production yield and magnetic characteristics for hard disk drives.
Patent Information
- Application Number
- JP2024058158
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-03-29
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2044-03-29
AI Technical Summary
The challenge in producing magnetic material targets for vertical magnetic recording in hard disk drives is the occurrence of oxide particles during sputter film formation, which leads to decreased yield due to adhesion to the substrate and difficulty in finely distributing oxides in the manufacturing process.
A magnetic material target composition containing specific concentrations of CO, Pt, Cr, Ru, and Ti, with controlled oxide distribution and size, along with a backing plate, to minimize oxide particle generation during sputter film formation.
The solution effectively suppresses oxide particle formation, enhancing magnetic characteristics and improving the production yield by ensuring fine distribution and controlled oxide sizes, thereby supporting high-quality thin film formation for magnetic recording media.
Smart Images

Figure 0007625112000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic material target and a magnetic material target assembly, and mainly to a magnetic material target for the production of a membrane for a HDD. [Background technology]
[0002] The layers constituting hard disk drives (HDDs) that employ perpendicular magnetic recording are made of materials based on ferromagnetic metals such as Co, Fe, and Ni, and the recording layers are often made of composite materials consisting of ferromagnetic alloys such as Co-Cr, Co-Pt, and Co-Cr-Pt, which are mainly composed of Co, and non-magnetic inorganic materials. Thin films for magnetic recording media such as hard disk drives are often produced by sputtering magnetic targets containing the above materials, due to their high productivity.
[0003] In general, magnetic material targets are manufactured by first crushing and mixing raw material powders, and then hot pressing the resulting mixture to obtain a sintered body. After this, in order to increase the density of the sintered body, HIP (Hot Isostatic Pressing) processing may be performed. The sintered body thus obtained is processed by a lathe to manufacture a target of a predetermined shape (Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6445126 [Patent Document 2] Patent No. 6332869 [Patent Document 3] Patent No. 6958819 Summary of the Invention [Problem to be solved by the invention]
[0005] As mentioned above, composite materials consisting of ferromagnetic alloys mainly composed of Co and non-magnetic inorganic materials are useful as recording layers for HDDs, and are sputter-deposited by HDD media manufacturers to form thin films with a granular structure in which magnetic particles are separated by oxide grain boundaries. In recent years, there has been a trend toward increasing the proportion of B oxides in the added oxides in perpendicular magnetic recording media that use Co as the main component of magnetic particles.
[0006] One of the problems in sputtering a magnetic material target containing oxides and mainly composed of Co is the generation of arcing from coarse oxides. If particles are generated from arcing and adhere to the substrate, the yield of the media decreases. For this reason, in the manufacture of a magnetic material target containing oxides and mainly composed of Co, it has been important to manufacture a target in which oxides are finely dispersed in the master alloy phase. On the other hand, the oxide of B is a low-melting material among the oxide species added in the manufacture of a magnetic material target containing oxides and mainly composed of Co, and the amount of B oxide added has been increasing in recent years. For this reason, it has become difficult to manufacture a target in which oxides are finely dispersed using conventional techniques, and particles are more likely to be generated during sputtering.
[0007] Therefore, an object of an embodiment of the present invention is to provide a magnetic material target and a magnetic material target assembly that contain oxides and that are mainly composed of Co, in which the generation of particles during sputtering film formation is effectively suppressed. [Means for solving the problem]
[0008] The above problems are solved by the present invention, which is specified as follows. 1. One or more of Pt, Cr, Ru, B, and Ti; An oxide, and the balance being Co and optionally containing impurities; The total concentration of Co, Pt, Cr, Ru, and Ti is 50 at% or more, The concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more, The oxide comprises an oxide of B, A magnetic material target, wherein the area-weighted average diameter of the oxide calculated assuming the shape of the oxide to be circular is 1.3 μm or less. 2. Observation field area: 11569μm 2 2. The magnetic material target according to claim 1, wherein the number of the oxide particles per unit area is 5,000 or more. 3. Observation field area: 11569μm 2 The total area of the oxide per unit area is 1900 μm 2 3. The magnetic material target according to 1 or 2 above, which is: 4. The magnetic material target according to any one of 1 to 3 above, wherein the oxide further contains one or more oxides of elements selected from Al, Si, Ba, Be, Ca, Ce, Cr, Co, Dy, Er, Eu, Ga, Gd, Ho, Li, Mg, Mn, Nb, Nd, Pr, Sc, Sm, Sr, Ta, Tb, Ti, V, Y, Zn, and Zr. 5. A magnetic material target according to any one of 1 to 4 above, a backing plate bonded to the magnetic material target; 1. A magnetic material target assembly comprising: Effect of the Invention
[0009] According to an embodiment of the present invention, it is possible to provide a magnetic material target and a magnetic material target assembly that contain oxides and that are mainly composed of Co, in which generation of particles during sputtering film formation is effectively suppressed. [Brief description of the drawings]
[0010] [Figure 1] This shows an example of a binarized image and the original image in image analysis using ImageJ. [Diagram 2] This is a screenshot of the settings for binarization processing using ImageJ. [Diagram 3] 1 is a SEM image of Example 1. [Figure 4] 1 is an SEM image of Example 2. [Diagram 5]1 is a SEM image of Example 3. [Figure 6] 1 is an SEM image of Example 4. [Figure 7] 1 is an SEM image of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Next, the embodiments of the present invention will be described in detail with reference to the drawings. It should be understood that the present invention is not limited to the following embodiments, and that appropriate changes and improvements in the design may be made based on the ordinary knowledge of those skilled in the art without departing from the spirit of the present invention.
[0012] <Magnetic material target> The shape of the magnetic material target according to the embodiment of the present invention is not particularly limited, and may be a flat plate (including a disk or rectangular plate), a cylindrical shape, or any other shape.
[0013] The magnetic material target according to the embodiment of the present invention contains at least one of Pt, Cr, Ru, and Ti, an oxide, and the balance is Co and selectively contained impurities. By using the magnetic material target according to the embodiment of the present invention as a sputtering target, a thin film for a magnetic recording medium such as a hard disk drive (HDD) can be produced.
[0014] In the magnetic material target according to the embodiment of the present invention, the total concentration of Co, Pt, Cr, Ru, and Ti is 50 at% or more. When the total concentration of Co, Pt, Cr, Ru, and Ti in the magnetic material target is 50 at% or more, the magnetic properties are improved. The upper limit of the total concentration of Co, Pt, Cr, Ru, and Ti in the magnetic material target is not particularly limited, but is preferably 90 at% or less from the viewpoint of securing the grain boundary material. Moreover, the total concentration of Co, Pt, Cr, Ru, and Ti in the magnetic material target is more preferably 50 to 85 at%, and even more preferably 50 to 80 at%. Moreover, the concentration of Cr is preferably 10 at% or less, and more preferably 7 at% or less.
[0015] In the magnetic material target according to the embodiment of the present invention, the concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more. With such a configuration, a particularly preferable magnetic thin film can be obtained. In the magnetic material target according to the embodiment of the present invention, the concentration of B is preferably 10 to 16 at%, and more preferably 11 to 15 at%. In the magnetic material target according to the embodiment of the present invention, the concentration of O is preferably 15 to 28 at%, and more preferably 16 to 26 at%.
[0016] The magnetic material target according to the embodiment of the present invention contains, as an oxide, an oxide of B. An example of the oxide of B is B2O3. Here, how to determine whether B is contained in the form of B2O3 in the magnetic material target according to the embodiment of the present invention will be described below. First, the magnetic material target is cut and the cross section is mirror-polished to obtain a sample for microstructure observation. More specifically, the cross section of the magnetic material target is polished in sequence using abrasive cloths and papers with grit sizes ranging from P80 to P2000, and finally buffed with aluminum oxide abrasive grains with a particle size of 0.3 μm to obtain a sample for microstructure observation having a cross-sectional polished surface. In addition, at this time, aluminum oxide and granular polishing debris attached to the polished surface are removed by washing. Next, element mapping is performed by performing WDX mapping analysis (Wave Length-dispersive X-ray Mapping Spectroscopy) in a field of view of 50 μm × 50 μm using FE-EPMA (Field Emission-Electron Probe Micro Analysis) on the sputtered surface of the sample after mirror polishing. The WDX mapping analysis in a field of view of 50 μm × 50 μm using FE-EPMA was performed at an acceleration voltage of 15.0 kV and an irradiation current of 2.0 × 10 -8 This can be done by performing a stage scan under the condition of A. At this time, if the areas where the detection intensity of B and O are high coincide with each other, it is considered that the B is mostly present in the sintered body as an oxide. Therefore, B where the area where the detection intensity is high coincides with O is judged to be present in the form of B2O3. In addition to B2O3, the oxide may further contain one or more oxides of elements selected from Al, Si, Ba, Be, Ca, Ce, Cr, Co, Dy, Er, Eu, Ga, Gd, Ho, Li, Mg, Mn, Nb, Nd, Pr, Sc, Sm, Sr, Ta, Tb, Ti, V, Y, Zn, and Zr in order to further improve the magnetic properties.
[0017] In the magnetic material target according to the embodiment of the present invention, the volume fraction of oxide is preferably 30 vol.% or more. When the volume fraction of oxide in the magnetic material target is 30 vol.% or more, the magnetic properties are further improved. There is no particular upper limit to the volume fraction of oxide in the magnetic material target, but from the viewpoint that the magnetic properties deteriorate when there is too much oxide, it is preferably 60 vol.% or less. Moreover, the volume fraction of oxide in the magnetic material target is more preferably 30 to 55 vol.%, and even more preferably 30 to 50 vol.%. The volume fraction of oxide can be calculated from the composition of the target, and the volume of each component contained in the target is calculated by (content of each material: mol) x (molecular weight of each material: g / mol) x (reciprocal of density of each material: cm 3 Next, the volume fraction of oxides can be calculated by dividing the total volume of only oxides among the components by the total volume of all components.
[0018] The remainder of the magnetic material target according to the embodiment of the present invention may or may not contain impurities. Examples of the impurities include metal elements such as Fe, Ni, Cu, Zr, Al, W, V, Zn, Cu, Zn, Sn, and Ta, and elements such as C or N from gas components such as carbon dioxide and nitrogen in the atmosphere, or compounds thereof. The content of the impurities contained in the remainder of the magnetic material target according to the embodiment of the present invention may be 0.5 mol% or less, or may be 0.15 mol% or less. In addition, the impurities can be analyzed by taking an analysis sample from the magnetic material target and using infrared absorption spectrometry, an ICP optical emission spectrometer, GDMS (glow discharge mass spectrometry), or the like. The amount and shape of the analysis sample vary depending on the analysis method used, and the optimal amount and shape for each method can be selected.
[0019] In the magnetic material target according to the embodiment of the present invention, the area-weighted average diameter of the oxide calculated assuming that the shape of the oxide is a circle is 1.3 μm or less. In the magnetic material target according to the embodiment of the present invention, as described above, the oxide contains an oxide of B, the concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more. In general, if the concentration of oxygen is high, there is a high possibility that coarse oxides will be contained, and in that case, arcing is likely to occur during sputtering film formation, and there is a problem of particles being generated. In contrast, in the magnetic material target according to the embodiment of the present invention, the concentration of O is 13.5 at% or more, while the area-weighted average diameter of the oxide calculated assuming that the shape of the oxide is a circle is controlled to 1.3 μm or less. Therefore, the structure of the oxide is sufficiently fine, and the occurrence of arcing during sputtering film formation is well suppressed. Since the sputtering rate of oxides is slower than that of metals, it is thought that the oxides will remain in the form of protrusions if sputtering discharge is performed for a long time. It is thought that arcing occurs due to electric field concentration on these protrusions. Here, it is considered that if the oxide structure is sufficiently fine, the remaining protrusions become small, so that electric field concentration is unlikely to occur and arcing is unlikely to occur. The area-weighted average diameter of the oxide calculated assuming that the shape of the oxide is circular is preferably 1.1 μm or less, more preferably 1.0 μm or less, and more preferably 0.9 μm or less. μm The lower limit of the area-weighted average diameter of the oxide calculated assuming that the shape of the oxide is a circle is not particularly limited, but may be 0.1 μm or more, 0.2 μm or more, 0.3 μm or more, 0.4 μm or more, 0.5 μm or more, or 0.6 μm or more.
[0020] A method for measuring the area-weighted average diameter of oxides calculated on the assumption that the shape of the oxides in the magnetic material target according to the embodiment of the present invention is circular will be described in detail. First, the magnetic material target is cut and the cross section is mirror-polished to obtain a sample for microstructural observation. More specifically, in the mirror-polishing, the cross section of the magnetic material target is polished in order using abrasive cloths and papers with grit sizes ranging from P80 to P2000, and finally buffed using aluminum oxide abrasive grains with a particle size of 0.3 μm to obtain a sample for microstructural observation having a polished cross section. In addition, at this time, the aluminum oxide and granular polishing debris adhering to the polished surface are thoroughly removed by washing. Next, a secondary electron image of the mirror-polished sputtered surface of the sample is taken using an FE-SEM (product name: SU3900, manufactured by Hitachi High-Tech Corporation) at an accelerating voltage of 15 kV and a magnification of 1000. In the secondary electron image, the metal matrix phase appears as a brighter area than the surrounding area, and the oxide appears as a darker area than the surrounding area. Next, the SEM image (field of view area 11569 μm 2 ) is binarized by the mode method using image processing software (ImageJ manufactured by the National Institutes of Health), and the area of each oxide is measured using the AnalyzePractiles function of the image processing software. The area S of each oxide obtained in this way is used to calculate the diameter D of each oxide using the following formula (1). Next, the area-weighted average diameter of the oxide is calculated using the following formula (2) for the area S and diameter D of each oxide.
[0021] JPEG0007625112000002.jpg10148
[0022] JPEG0007625112000003.jpg21164
[0023] The binarization using ImageJ is carried out according to the steps (1) to (5) below. (1) Click File → Open on the ImageJ toolbar to load an SEM image with a magnification of 1000x. (2) Select 8-bit from Image→Type. Draw a straight line along the scale bar, and select Analyze→Set scale to set the scale size. (3) Select the part of the image excluding the scale and cut out the scaled part by selecting Image → Crop. (4) Select Process→Filters→Gaussian Blur, enter 2 for Sigma, and click OK. (5) Select Process → Binary → Make Binary. This completes the binarization of the image. As described above, the areas that are darker than the surrounding areas that are classified as black by the binarization process are converted to black, and the black areas are considered to be oxides. The threshold for the binarization process is automatically set from the color histogram in the image. Figure 1 shows an example of an image binarized by ImageJ and the original image.
[0024] The magnetic material target according to the embodiment of the present invention has an observation field area of 11569 μm 2 In the magnetic material target according to the embodiment of the present invention, as described above, the area-weighted average diameter of the oxide calculated assuming that the shape of the oxide is a circle is 1.3 μm or less, and further, the number of oxide particles per observation field area is 11569 μm. 2 Since there are more than 5,000 oxide particles in this limited area, the oxide structure is sufficiently fine, and arcing during sputtering deposition is effectively suppressed. 2 The number of oxide particles per unit area is preferably 6000 or more, and more preferably 7000 or more. 2 The upper limit of the number of oxides per unit area is not particularly limited, but may be, for example, 30,000 or less, 25,000 or less, or 20,000 or less.
[0025] Observation field area of the magnetic material target according to the embodiment of the present invention is 11569 μm 2 A method for measuring the number of oxides per unit area will be described. As with the above-mentioned "Method for measuring the area-weighted average diameter of oxides calculated assuming that the oxide shape is circular," first, the magnetic material target is cut and the cross section is mirror-polished. Next, a secondary electron image is taken of the sputtered surface of the mirror-polished sample using an FE-SEM at an accelerating voltage of 15 kV and a magnification of 1000 times. Next, the captured SEM image (field of view area 11569 μm 2 ) is binarized by the mode method using image processing software (ImageJ), and the number of oxides is measured using the AnalyzePractiles function of ImageJ.
[0026] The magnetic material target according to the embodiment of the present invention has an observation field area of 11569 μm 2 The total oxide area per unit is 1900 μm 2 In the magnetic material target according to the embodiment of the present invention, as described above, the area-weighted average diameter of the oxide calculated assuming that the shape of the oxide is a circle is 1.3 μm or less, and further, the observation field area is 11569 μm 2 The total oxide area per unit is 1900 μm 2 By setting the total area of the oxide to 1600 μm or less, the area occupied by the oxide is small, so that the oxide structure is further finely refined, and the occurrence of arcing during sputtering deposition is more effectively suppressed. 2 More preferably, it is 1300 μm or less. 2 It is even more preferable that the observation field area is 11569 μm or less. 2 There is no particular need to set a lower limit for the total area of the oxide per unit area. For example, 2 It may be more than 200 μm 2 It may be more than 300 μm 2 It may be more than 400 μm 2 It may be more than 500 μm 2 It may be more than 600 μm 2 It may be more than 700 μm 2 It may be more than 800 μm 2 It may be more than 900 μm 2 It may be more than 1000 μm 2It may be more than 1100 μm 2 It may be more than that.
[0027] Observation field area of the magnetic material target according to the embodiment of the present invention is 11569 μm 2 A method for measuring the total oxide area per unit area will now be described. As with the above-mentioned "Method for measuring the area-weighted average diameter of oxides calculated assuming that the shape of the oxides in a magnetic material target is circular," first, the magnetic material target is cut and the cross section is mirror-polished. Next, a secondary electron image is taken of the sputtered surface of the mirror-polished sample using an FE-SEM at an accelerating voltage of 15 kV and a magnification of 1000 times. Next, the captured SEM image (field of view area 11569 μm 2 ) is binarized by the mode method using image processing software (ImageJ), and the total area of the oxide is measured using the AnalyzePractiles function of ImageJ. The specific procedure for binarization by the mode method using the above-mentioned image processing software (ImageJ) is as follows. Load the image from File→Open. Select 8-bit from Image→Type. Draw a straight line along the scale bar, and select Analyze→Set scale to set the scale size. Select the part of the image excluding the scale, and cut out the scaled part with Image→Crop. Select Process→Filters→Gaussian Blur, enter 2 for Sigma, and click OK. Select Process→Binary→Make Binary.
[0028] <Magnetic target assembly> The magnetic material target according to the embodiment of the present invention may be bonded to a backing plate as necessary to form a magnetic material target assembly. The magnetic material target assembly may be mounted on a sputtering device and used. As the brazing material, indium or indium tin may be used. The magnetic material target according to the embodiment of the present invention may be mounted on a sputtering device as it is without using a backing plate. The material of the backing plate is not particularly limited, and examples thereof include Cu, Ti, Mo, and alloys containing at least one of these (e.g., Cu-Ni-Si alloys (e.g., C18000, etc.), CuZn alloys, and CuCr alloys). The material of the backing plate preferably has a high thermal conductivity, and from this viewpoint, Cu is suitable.
[0029] <Method of manufacturing magnetic material target> Hereinafter, a method for manufacturing a magnetic material target according to an embodiment of the present invention will be described in detail. The magnetic material target according to the embodiment of the present invention can be manufactured by a powder sintering method. First, powders of each metal element are prepared. Also, instead of the powders of each metal element, alloy powders of these metals (for example, Co-Pt powder) may be used. In particular, it is preferable to use Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder. Note that using B2O3 powder as a raw material is not preferable because the obtained magnetic material target may contain coarse oxides. Regarding the 50% cumulative volume grain size D50 (average grain size D50) of each raw material powder, the following sizes can be used: Co powder: 1 to 10 μm, CrBO3 powder: 0.5 to 5 μm, Pt powder: 1 to 10 μm, Co2B2O5 powder: 1 to 20 μm, and Co2B powder: 1 to 50 μm. The purity of these raw materials is usually 2N (99 mass%) or more, preferably 3N (99.9 mass%) or more, and more preferably 4N (99.99 mass%) or more. If the purity is lower than 2N, the sintered body will contain a large amount of impurities, which may cause problems such as the failure to obtain the desired physical properties (for example, generation of particles due to arcing). These raw materials can be appropriately prepared based on the composition and purity of the desired sintered body.
[0030] These metal powders are then weighed out to obtain the desired composition, and mixed using a mixer that also serves as a grinder. As the mixer, a ball mill, a mortar, or the like can be used, but it is preferable to use a powerful mixing method such as a ball mill. In addition, in consideration of the problem of oxidation during mixing, it is preferable to mix in an inert gas atmosphere or in a vacuum.
[0031] Here, the mixing is performed by carrying out primary mixing, then sieving, and then secondary mixing. In the primary mixing, mixing is performed for 5 to 30 hours. In the secondary mixing, mixing is performed for 5 to 30 hours. By lengthening the mixing time of the raw materials, the area-weighted average diameter of the oxides calculated assuming that the shape of the oxides is a circle can be reduced, the number of oxides per a predetermined observation field area can be increased, and the total area of the oxides can be reduced. On the other hand, by shortening the mixing time of the raw materials, the area-weighted average diameter of the oxides calculated assuming that the shape of the oxides is a circle can be increased, the number of oxides per a predetermined observation field area can be reduced, and the total area of the oxides can be increased. In addition, by carrying out sieving between the primary mixing and the secondary mixing, coarse powder can be removed, and fine powder can be increased in the secondary mixing. As a result, coarsening of the oxides can be suppressed. The sieving is carried out using a sieve having an opening of 150 to 400 μm. From this viewpoint, by adjusting the mixing time of the raw materials, it is possible to control the area-weighted average diameter of the oxides calculated assuming that the shape of the oxides is circular, the number of oxides per predetermined observation field area, and the total area of the oxides.
[0032] The mixed powder thus obtained is molded and sintered using a hot press device to produce a sintered body. The molding and sintering are not limited to hot pressing, and plasma discharge sintering and hot isostatic sintering can also be used. The sintering conditions are 650 to 1400°C and 0.5 to 12 hours. By increasing the sintering temperature and / or lengthening the sintering time, the area-weighted average diameter of the oxides calculated assuming that the shape of the oxides is a circle can be increased, the number of oxides per a given observation field area can be reduced, and the total area of the oxides can be increased. On the other hand, by decreasing the sintering temperature and / or shortening the sintering time, the area-weighted average diameter of the oxides calculated assuming that the shape of the oxides is a circle can be reduced, the number of oxides per a given observation field area can be increased, and the total area of the oxides can be reduced. From this perspective, the area-weighted average diameter of the oxides calculated assuming that the shape of the oxides is a circle, the number of oxides per a given observation field area, and the total area of the oxides can be controlled by adjusting the sintering temperature and sintering time.
[0033] The sintered body is then removed from the hot press and subjected to HIP (Hot Isostatic Pressing). HIP is an effective means for increasing the density of the sintered body. The holding temperature during HIP is 650-1100°C, the holding time is 0.5-12 hours, and the pressure is 100 MPa or more. The sintered body thus obtained is then machined on a lathe into a desired shape to produce a magnetic material target.
[0034] <Film formation method using a magnetic material target> Using the magnetic material target according to the embodiment of the present invention, a thin film that mainly constitutes a magnetic recording medium can be formed. Specifically, a sputtering device is used to sputter the surface of the magnetic material target with accelerated argon ions, particles (sputtered particles) are released from the magnetic material target, and the sputtered particles are deposited on the surface of a substrate that is placed in a position opposite to the target, thereby forming a thin film on the surface of the substrate. The sputtering conditions can be appropriately set depending on the desired film thickness, composition, etc. EXAMPLES
[0035] The following examples of the present invention are provided for a better understanding of the present invention and its advantages, and are not intended to limit the invention.
[0036] <Example 1> The magnetic material target according to Example 1 was manufactured by the following manufacturing method. As raw material powders, 3N (99.9 mass%) Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were prepared and weighed to have a composition of Co-Pt-Cr-BO (Pt 10-20 at%, Cr 0.5-7 at%, B 11-15 at%, O 16-26 at%, Co (balance)). The raw material powders were prepared so that the total composition was 100 at%. The 50% cumulative volume particle size D50 (average particle size D50) of the raw material powders was as follows: Co powder: 4μm, CrBO3 powder: 1μm, Pt powder: 3μm, Co2B2O5 powder: 8μm, Co2B powder: 3μm Next, the weighed Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were placed in a ball mill pot together with zirconia balls, and primary mixing was performed for 10 hours, sieving through a sieve with 150 μm openings, and secondary mixing for 10 hours was performed in that order.
[0037] Next, the mixed powder taken out of the ball mill pot was filled into a carbon mold and hot pressed. The hot pressing conditions were a vacuum atmosphere, a heating rate of 300°C / hour, a holding temperature (sintering temperature) of 800°C, and a holding time (sintering time) of 2 hours, and the material was pressurized at 30 MPa from the start of heating to the end of holding. After the holding, the material was allowed to cool naturally in the chamber. Then, the sintered body taken out of the hot pressing mold was subjected to HIP processing. The HIP processing conditions were a heating rate of 300°C / hour, a holding temperature of 750°C, and a holding time of 2 hours, and the gas pressure of Ar gas was gradually increased from the start of heating, and the material was pressurized at 150 MPa during holding. After the holding, the material was allowed to cool naturally in the furnace. In this way, the magnetic material target according to Example 1 was produced.
[0038] <Example 2> The magnetic material target according to Example 2 was manufactured by the following manufacturing method. As raw material powders, 3N (99.9 mass%) Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were prepared and weighed to have a composition of Co-Pt-Cr-BO (Pt 10-20 at%, Cr 0.5-7 at%, B 11-15 at%, O 16-26 at%, Co (balance)). The raw material powders were prepared so that the total composition was 100 at%. The 50% cumulative volume particle size D50 (average particle size D50) of the raw material powders was as follows: Co powder: 4μm, CrBO3 powder: 1μm, Pt powder: 3μm, Co2B2O5 powder: 8μm, Co2B powder: 30μm Next, the weighed Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were placed in a ball mill pot together with zirconia balls, and primary mixing was performed for 10 hours, sieving through a sieve with 150 μm openings, and secondary mixing for 10 hours was performed in that order.
[0039] Next, the mixed powder taken out of the ball mill pot was filled into a carbon mold and hot pressed. The hot pressing conditions were a vacuum atmosphere, a heating rate of 300°C / hour, a holding temperature (sintering temperature) of 800°C, and a holding time (sintering time) of 2 hours, and the material was pressurized at 30 MPa from the start of heating to the end of holding. After the holding, the material was allowed to cool naturally in the chamber. Then, the sintered body taken out of the hot pressing mold was subjected to HIP processing. The HIP processing conditions were a heating rate of 300°C / hour, a holding temperature of 750°C, and a holding time of 2 hours, and the gas pressure of Ar gas was gradually increased from the start of heating, and the material was pressurized at 150 MPa during holding. After the holding, the material was allowed to cool naturally in the furnace. In this way, a magnetic material target according to Example 2 was produced.
[0040] <Example 3> The magnetic material target according to Example 3 was manufactured by the following manufacturing method. As raw material powders, 3N (99.9 mass%) Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were prepared and weighed to have a composition of Co-Pt-Cr-BO (Pt 10-20 at%, Cr 0.5-7 at%, B 11-15 at%, O 16-26 at%, Co (balance)). The raw material powders were prepared so that the total composition was 100 at%. The 50% cumulative volume particle size D50 (average particle size D50) of the raw material powders was as follows: Co powder: 4μm, CrBO3 powder: 1μm, Pt powder: 3μm, Co2B2O5 powder: 8μm, Co2B powder: 3μm Next, the weighed Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were placed in a ball mill pot together with zirconia balls, and primary mixing was performed for 8 hours, sieving through a sieve with 150 μm openings, and secondary mixing for 8 hours was performed in that order.
[0041] Next, the mixed powder taken out of the ball mill pot was filled into a carbon mold and hot pressed. The hot pressing conditions were a vacuum atmosphere, a heating rate of 300°C / hour, a holding temperature (sintering temperature) of 800°C, and a holding time (sintering time) of 2.5 hours, and the material was pressurized at 30 MPa from the start of heating to the end of holding. After the holding, the material was allowed to cool naturally in the chamber. Then, the sintered body taken out of the hot pressing mold was subjected to HIP processing. The HIP processing conditions were a heating rate of 300°C / hour, a holding temperature of 750°C, and a holding time of 2 hours, and the gas pressure of Ar gas was gradually increased from the start of heating, and the material was pressurized at 150 MPa during holding. After the holding, the material was allowed to cool naturally in the furnace. In this way, a magnetic material target according to Example 3 was produced.
[0042] <Example 4> The magnetic material target according to Example 4 was manufactured by the following manufacturing method. As raw material powders, 3N (99.9 mass%) Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were prepared and weighed to have a composition of Co-Pt-Cr-BO (Pt 10-20 at%, Cr 0.5-7 at%, B 11-15 at%, O 16-26 at%, Co (balance)). The raw material powders were prepared so that the total composition was 100 at%. The 50% cumulative volume particle size D50 (average particle size D50) of the raw material powders was as follows: Co powder: 4μm, CrBO3 powder: 1μm, Pt powder: 3μm, Co2B2O5 powder: 8μm, Co2B powder: 3μm Next, the weighed Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were placed in a ball mill pot together with zirconia balls, and primary mixing was performed for 10 hours, sieving through a sieve with 150 μm openings, and secondary mixing for 10 hours was performed in that order.
[0043] Next, the mixed powder taken out of the ball mill pot was filled into a carbon mold and hot pressed. The hot pressing conditions were a vacuum atmosphere, a heating rate of 300°C / hour, a holding temperature (sintering temperature) of 750°C, and a holding time (sintering time) of 3 hours, and the material was pressurized at 30 MPa from the start of heating to the end of holding. After the holding was completed, the material was allowed to cool naturally in the chamber. Then, the sintered body taken out of the hot pressing mold was subjected to HIP processing. The HIP processing conditions were a heating rate of 300°C / hour, a holding temperature of 750°C, and a holding time of 2 hours, and the gas pressure of Ar gas was gradually increased from the start of heating, and the material was pressurized at 150 MPa during holding. After the holding was completed, the material was allowed to cool naturally in the furnace. In this way, a magnetic material target according to Example 4 was produced.
[0044] <Comparative Example 1> A magnetic material target according to Comparative Example 1 was manufactured by the following manufacturing method. As raw material powders, 3N (99.9 mass%) Co powder, CrBO3 powder, Pt powder, and B2O3 powder were prepared and weighed to have a composition of Co-Pt-Cr-BO (Pt 10-20 at%, Cr 0.5-7 at%, B 11-15 at%, O 16-26 at%, Co (balance)). The raw material powders were prepared so that the total composition was 100 at%. The 50% cumulative volume particle size D50 (average particle size D50) of the raw material powders was as follows: Co powder: 4μm, CrBO3 powder: 1μm, Pt powder: 3μm, B2O3 powder: 10μm Next, the weighed Co powder, CrBO3 powder, Pt powder, and B2O3 powder were placed in a ball mill pot together with zirconia balls, and the mixture was subjected to primary mixing for 12 hours, sieving through a sieve with 150 μm openings, and secondary mixing for 5 hours, in that order.
[0045] Next, the mixed powder taken out of the ball mill pot was filled into a carbon mold and hot pressed. The hot pressing conditions were a vacuum atmosphere, a heating rate of 300°C / hour, a holding temperature (sintering temperature) of 800°C, and a holding time (sintering time) of 2 hours, and the material was pressurized at 30 MPa from the start of heating to the end of holding. After the holding, the material was naturally cooled in the chamber. Then, the sintered body taken out of the hot pressing mold was subjected to HIP processing. The HIP processing conditions were a heating rate of 300°C / hour, a holding temperature of 750°C, and a holding time of 2 hours, and the gas pressure of Ar gas was gradually increased from the start of heating, and the material was pressurized at 150 MPa during holding. After the holding, the material was naturally cooled in the furnace. In this way, a magnetic material target according to Comparative Example 1 was produced.
[0046] -Evaluation of the area-weighted average diameter of oxides calculated assuming the shape of oxides is circular Each of the magnetic material targets of Examples 1 to 4 and Comparative Example 1 was cut and the cross section was mirror-polished to obtain a sample for observing the structure. Next, secondary electron images of the sputtered surface of the mirror-polished sample were taken using an FE-SEM (product name: SU3900, manufactured by Hitachi High-Tech Corporation) at an accelerating voltage of 15 kV and a magnification of 1000. The taken SEM images are shown in Figure 3 (Example 1), Figure 4 (Example 2), Figure 5 (Example 3), Figure 6 (Example 4), and Figure 7 (Comparative Example 1), respectively. Next, the SEM image (field of view area 11569 μm 2 ) was binarized by the mode method using image processing software (ImageJ manufactured by the National Institutes of Health), and the area of each oxide was measured using the AnalyzePractiles function of the image processing software. From the area S of each oxide thus obtained, the diameter D of each oxide was calculated using the following formula (1). Next, from the area S and diameter D of each oxide, the area-weighted average diameter of the oxide was calculated using the following formula (2).
[0047] JPEG0007625112000004.jpg20162
[0048] JPEG0007625112000005.jpg10148
[0049] The above ImageJ binarization was carried out according to the steps (1) to (5) below. (1) Click File → Open on the ImageJ toolbar to load an SEM image with a magnification of 1000x. (2) Select 8-bit from Image→Type. Draw a straight line along the scale bar, and select Analyze→Set scale to set the scale size. (3) Select the part of the image excluding the scale and cut out the scaled part by selecting Image → Crop. (4) Select Process→Filters→Gaussian Blur, enter 2 for Sigma, and click OK. (5) Select Process → Binary → Make Binary. This completes the binarization of the image. A screenshot of the setting conditions is shown in Figure 2. As described above, after importing the SEM image with ImageJ, a binarization process was performed to convert the areas on the SEM image that were darker than the surrounding areas that were classified as black by the binarization process to black, and the black areas were considered to be oxides. The area S of the black areas was calculated, and the diameter D of each oxide was calculated using the obtained area S according to the above formula (1), and the area-weighted average diameter of the oxides was calculated according to the above formula (2) based on the area S and diameter D of each oxide.
[0050] Observation field area: 11569μm 2 Evaluation of the number of oxides per unit area In the same manner as in the above-mentioned "Evaluation of the area-weighted average diameter of oxides calculated assuming that the shape of oxides is circular," for the samples for microstructural observation of Examples 1 to 4 and Comparative Example 1, secondary electron images of the sputtered surfaces of the samples after mirror polishing were taken using an FE-SEM at an accelerating voltage of 15 kV and a magnification of 1000 times. Next, the SEM image (field of view area 11569 μm 2) was binarized by the mode method using ImageJ. Areas on the SEM image that were classified as black by the binarization process and were darker than the surrounding areas were converted to black, and the black areas were considered to be oxides, and the number of black areas was calculated.
[0051] Observation field area: 11569μm 2 Evaluation of total oxide area per In the same manner as in the above-mentioned "Evaluation of the area-weighted average diameter of oxides calculated assuming that the shape of oxides is circular," for the samples for microstructural observation of Examples 1 to 4 and Comparative Example 1, secondary electron images of the sputtered surfaces of the samples after mirror polishing were taken using an FE-SEM at an accelerating voltage of 15 kV and a magnification of 1000 times. Next, the SEM image (field of view area 11569 μm 2 ) was binarized by the mode method using ImageJ. Areas on the SEM image that were darker than the surrounding areas and classified as black by the binarization process were converted to black, and the black areas were considered to be oxides, and the total area of the black areas was measured using the AnalyzeParticles function of ImageJ.
[0052] A magnetic material target was manufactured by a composition and manufacturing method similar to those of Examples 1 to 4, and a WDX mapping analysis was performed in a field of view of 50 μm × 50 μm by FE-EPMA. The areas where the detection intensity of B and O was high were consistent. Therefore, it is considered that the magnetic material target contains an oxide of B. Therefore, it is expected that the magnetic material targets of Examples 1 to 4, which are examples of targets manufactured by a composition and manufacturing method similar to those of the test example, also contain an oxide of B. In addition, since the raw material powder in Comparative Example 1 contains B2O3 powder, it is expected that the magnetic material target of Comparative Example 1 also contains an oxide of B.
[0053] Particle evaluation The particle evaluation was carried out as follows. First, the magnetic material targets according to Examples 1 to 4 and Comparative Example 1 were cut by a lathe to a shape of 165.1 mm in diameter and 4.0 mm in thickness to prepare disk-shaped targets. These were attached to a magnetron sputtering device (C-3010 sputtering system manufactured by Canon Anelva Corporation) and sputtering was performed. The sputtering conditions were an input power of 1 kW and an Ar gas pressure of 1.7 Pa. After performing pre-sputtering at 1 kWhr, a film was formed on a 4-inch silicon substrate for 20 seconds. Next, for each of Examples 1 to 4, the number of particles with a particle size of 0.09 μm or more that adhered to the substrate was measured using a particle counter. A Candela CS920 (manufactured by KLA Tencor Corporation) was used as the particle counter. A laser was irradiated onto the wafer on which a film was formed by sputtering, and the particles were identified by detecting the reflection and scattering of the laser.
[0054] [Table 1]
[0055] <Consideration> According to Table 1, the magnetic material targets according to Examples 1 to 4 each contained Pt, Cr, B, and an oxide, with the balance being Co, the total concentration of Co, Pt, and Cr was 50 at% or more, the concentration of B was 9 at% or more, the concentration of O was 13.5 at% or more, and the oxide of B was contained, and the area-weighted average diameter of the oxide calculated assuming the shape of the oxide to be a circle was 1.3 μm or less. Therefore, the generation of particles during sputtering film formation was effectively suppressed. In contrast, in the magnetic material target according to Comparative Example 1, the area-weighted average diameter of the oxide calculated assuming the shape of the oxide to be circular exceeded 1.3 μm, and therefore the generation of particles during the sputtering film formation could not be suppressed.
[0056] According to one embodiment of the present invention, a magnetic material target and a magnetic material target assembly containing oxides and mainly composed of Co, in which particle generation during sputtering film formation is well suppressed, can be obtained, which may contribute to the sophistication of thin film formation technology by sputtering used in the manufacture of magnetic recording hard disk media, etc. Therefore, one embodiment of the present invention may contribute to Goal 9 of the Sustainable Development Goals (SDGs) led by the United Nations, "Build resilient infrastructure, promote inclusive and sustainable industrialization, and foster innovation."
Claims
1. One or more of Pt, Cr, Ru, B, and Ti; An oxide of B; with the balance being Co and optionally containing impurities; Co is the main component, The total concentration of Co, Pt, Cr, Ru, and Ti is 50 at% or more; The concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more, The area-weighted average diameter of the oxide calculated assuming the shape of the oxide to be a circle is 1.3 μm or less, A magnetic material target, wherein the total area of the oxides per observation field area of 11,569 μm 2 is 1,900 μm 2 or less.
2. Observation field area: 11569 μm 2 The magnetic material target according to claim 1 , wherein the number of said oxide particles per unit area is 5,000 or more.
3. A magnetic material target as described in claim 1, further containing one or more oxides of elements selected from Al, Si, Ba, Be, Ca, Ce, Cr, Co, Dy, Er, Eu, Ga, Gd, Ho, Li, Mg, Mn, Nb, Nd, Pr, Sc, Sm, Sr, Ta, Tb, Ti, V, Y, Zn, and Zr.
4. The magnetic material target according to any one of claims 1 to 3, a backing plate bonded to the magnetic material target; 1. A magnetic material target assembly comprising:
Citation Information
Patent Citations
Origanic electrolyte cell
JP1988032869A
Manufacture of gaas compound semiconductor substrate
JP1989045126A
Target, method for manufacturing target, and method for manufacturing magnetic recording medium
JP2012033247A
Perpendicular magnetic recording medium, method of producing perpendicular magnetic recording medium, and perpendicular recording and reproducing device
JP2015153447A
Sputtering targets for magnetic recording media
JP6958819B2